Construction Of Recombinant OTBU1 Knockdown In Breast, Bone And Liver Cancer Cell Lines - Noor, Nor Shila Mohamed (2019)
Cancer is one of the leading causes of mortality and morbidity all over the world. Various types of cancer-causing genetic aberrations are well characterized such as mutations, gene amplification, translocation, structural deletion and chromosomal mis-segregation. With the use of modern genomic technologies, we are now beginning to understand the enormous complexity of cancer. The growing understanding of cancer cell biology and tumor progression is gradually leading to better methods for treating the disease. The emergence of genome editing tools offers an exciting solution to addressing this issue by disrupting expression of cancer genes. In this study, the current genome editing tool, CRISPR/Cas9 system, is used to demonstrate its potential in disrupting the expression of OTUB1 gene in breast, bone and liver cancer cells. OTUB1 gene is ubiquitously expressed in human tissues and play an important role in many physiological and pathological processes of human. OTUB1 is also strongly correlated with cancer progression. Prior to transfection to knockdown OTUB1, optimization of transfection procedure and transfection efficacy in cell lines need to be done to get optimum results. Analysis using fluorescence microscopy and flow cytometry showed that Lipofectamine 3000 is a preferable method in transfection. These encouraging results will enable us to conduct further investigations on exploring the role of OTUB1 gene in signalling pathways of different cancer cells. These results showed that the recombinant DNA successfully constructed to knockdown OTUB1 using CRISPR/Cas9 system can be a promising tool for cancer treatment strategies in the future.